Phytoremediation: Synergistic Effect of Thalia geniculata and Crassipes Eichhornia (Water Hyacinth) During Domestic Wastewater Treatment - Yovo, Franck; DIMON, BIAOU FIDÈLE; SUANON, Fidèle; Eni, Coffi Azandegbe; Agani, Ignace Chabi; Wotto, Valentin (My University, 2017)
The treatment of wastewater and removal of pollutants before discharge into natural water reserves, remain a major concern of the 21th century. Many of treatment techniques based on phytoremediation present limits regarding the treatment efficiency. In order to improve the efficiency of nutrients abatement in gray water, the synergy between Thalia geniculata and Crassipes Eichhornia (water hyacinth) was studied. Three treatments: Thalia geniculata (TG), water hyacinth (JE) and the combination of the two [Thalia geniculata and water hyacinth, (TJ)] in three different basins have been setup for the treatment of domestic wastewater. The water physicochemical parameters and nutrients concentrations were determined during the treatment process. After twelve days of treatment, results revealed a remarkable reduction of pollutants (NO3 -, NTK and PO4 3-) in the basins TG and JE, with removal efficiencies of (68.62%, 55.71%, 23.55%) and (53.98%; 39.52%; 89.27%), respectively. As for the treatment combining the two species (TJ), the yield of pollutants abatement was 97.75% for NO3 -, 82.83% for NTK and 24.84% for PO4 3-. An excellent treatment performance of the basin TJ was noticed regarding nitrogen removal against phosphate (PO4 3-) which was poorly removed. Accordingly, the results indicated an interesting synergistic effect between TG and JE; with the dominance of the TG tendency to remove nutrient (NO3 -) from wastewater. The observed synergistic effect of Thalia geniculata and water hyacinth could be effective and promising for the sequestration of nitrogen in domestic wastewater within a couple of days. However, further studies are still needed to better understand the mechanism governing the removal of nitrogen to the detriment of phosphate when combining the two species.
Keywords: Phytoremediation; Domestic Wastewater; Synergy Effect; Pollutants; Thalia geniculata; Eichhornia Crassipes